The effectiveness of local anesthesia of the trocar wound area in the correction of postoperative pain syndrome in colorectal oncosurgery - A. A. Zakharenko; O. A. Ten; P. V. Zverev; A. A. Orlova; Yu. S. Polushin (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Severe pain syndrome is a significant complication of the postoperative period. Despite the prevalence of laparoscopic surgical interventions for colorectal cancer, there is still a lack of commonly agreed strategies to provide the most effective perioperative analgesia in such patients. Multimodal analgesia is a modern method of anesthesia that affects multiple components of the pathogenesis of pain syndrome. Proposed as a gold standard for open colorectal surgeries, thoracic epidural anesthesia as a component of multimodal analgesia does not show the same beneficial results in laparoscopic colorectal intervention.The OBJECTIVE was to compare different techniques of local anesthesia and to identify the most perspective method of local anesthesia as a part of a multimodal analgesia in terms of effectiveness and affordability in daily practice.METHODS AND MATERIALS. A review of the current scientific literature was conducted in order to search and assess the usability of different local anesthesia techniques.CONCLUSION. Infiltration of a local anesthetic solution into the trocar wound area is the most uncomplicated and affordable method of anesthesia, comparable in efficacy with other methods of locoregional anesthesia, which can potentially be a promising component of multimodal analgesia in colorectal oncosurgery.